EduGame Maru: Application for Early Mathematics Learning as an Alternative for Optimizing Cognitive Ability for 4-6 Years Children - Rr Deni Widjayatri; Lizza Suzanti; Nenden Sundari; Yulianti Fitriani; Rika Ar Nurazka; Firda Rahmadini; Ria Yuliati Ichsan; Nabila Qotrunnida (Universitas Pendidikan Indonesia Kampus Serang, 2022)
Mathematics teaching process in kindergarten must adapt to the pandemic situation which require learning from distance. This research develops an Android-based application for learning mathematical concepts, named EduGame Maru, consisting of five types of games: recognizing numbers, algebra, statistics, geometry, and probability. This research aimed to create an interactive, innovative, and practical application as a digital medium. The method used in this research was the RD model, with 4D development (define, design, develop, and disseminate). The EduGame Maru application received a validation result of